Assessment of success of introduction of wood and shrubby plants in the conditions of the Zhezkazgan industrial region - Maksutbekova, G.T.; Akhmatov, M.K. (Fundamental and Experimental Biology, 2017)
At the article experience of introduction of woody plants in the Central Kazakhstan is analyzed. Modification of introduction division of the region and classification of groups of ecological plasticity of species of introduced species in the region is offered. The validity and efficiency of these developments is confirmed with the analysis of use of plants in green construction of the Central Kazakhstan. The principles of introduction mobilization of plants to the Central Kazakhstan are developed. Following the results of researches all trees have been broken into 4 categories: 1 — very perspective plants which can be applied widely in mass gardening of settlements of the Zhezkazgan region; 2 — perspective species which can be used for landing by the square and when gardening a park zone; 3 — unpromising species, suitable for creation of separate compositions and in private gardening; 4 — not perspective species demanding careful leaving and suitable only in private gardening and green construction.